The open-air site La Sénétrière and the Gravettian in the southern Burgundy (Saône-et-Loire, France). (20th June 2021) - Nordwald, Elina; Floss, Harald
Abstract: In the Mâconnais, southern Burgundy, a number of paleolithic sites are concentrated along the river Saône. One of these is the prehistoric open-air site La Sénétrière. This contribution gives an overview of recently conducted research and its results, focusing on stone artifacts from surface finds attributed to the Upper Paleolithic, including a considerable amount of blade cores. This paper summarizes the results of a master's thesis on the site's Upper Paleolithic core technology completed last year. For this purpose, these cores were divided into seven individual categories in order to be able to trace the respective core and blank production. Therefore, working stage analyses were carried out on ten cores. In addition, a comparison was conducted in which further sites with a similar technological component and possible identical core categories were compared with the cores from La Sénétrière. In combination with a classical attribute analysis, information could be obtained about a possible chronological classification and function of the site, to interpret La Sénétrière more precisely. In the past, the Upper Paleolithic component of the lithic artifacts was dated to the Perigordian V. However, our analyses show that Aurignacian artifacts are also present. Thus, the site was inhabited for a longer time than previously assumed. The dating of the confirmed Gravettian artifacts was reduced to an age of 33, 000–28, 000 calBP by comparing the sites, their diagnostic artifacts and core categories.